The energy paradox of sectoral change and the future prospects of the service economy - Christian Gross; Ulrich Witt (Max Planck Institute of Economics, 2012)
Persistently rising energy prices have revived interest in the economic impact of changing energy costs. We explore the effects of these costs on sectoral change, particularly in relation to the rise and future prospects of the service economy. Following Baumol's cost disease hypothesis, (unexplained) productivity differentials between the industrial and service sectors are often utilized to explain the recent dominance of the service sector. We hypothesize that the productivity differential results from the respective technological opportunities for substituting energy for labor in each of the sectors. To test our hypothesis, we analyze the U.S. economy for the period from 1970 to 2005. By means of the Autoregressive Distributed Lags (ARDL) bounds test, we examine whether a cointegrating relationship exists, in a given sector, between labor productivity and variables from our model representing the technological substitution conditions. Our findings support this hypothesis. Therefore, we can conclude that productivity differentials between the sectors may vanish if, as a result of rising energy costs, the substitution incentives are likely to fade out. Such a development might put the future of the service economy at risk.
Keywords: D24; O41; O47; Q43; Q57; 330; Sectoral Change; Energy; Technical Change; Productivity Growth; Baumol's disease; Energiepreis; Strukturwandel; Drei-Sektoren-Hypothese; Arbeitsproduktivität; Produktionskosten; Schätzung; USA